Kelvin probe force microscopy for local characterisation of active nanoelectronic devices - Wagner, Tino; Beyer, Hannes; Reissner, Patrick; Mensch, Philipp; Riel, Heike; Gotsmann, Bernd; Stemmer, Andreas (Beilstein Journal of Nanotechnology, 2015)
Frequency modulated Kelvin probe force microscopy (FM-KFM) is the method of choice for high resolution measurements of local surface potentials, yet on coarse topographic structures most researchers revert to amplitude modulated lift-mode techniques for better stability. This approach inevitably translates into lower lateral resolution and pronounced capacitive averaging of the locally measured contact potential difference. Furthermore, local changes in the strength of the electrostatic interaction between tip and surface easily lead to topography crosstalk seen in the surface potential. To take full advantage of the superior resolution of FM-KFM while maintaining robust topography feedback and minimal crosstalk, we introduce a novel FM-KFM controller based on a Kalman filter and direct demodulation of sidebands. We discuss the origin of sidebands in FM-KFM irrespective of the cantilever quality factor and how direct sideband demodulation enables robust amplitude modulated topography feedback. Finally, we demonstrate our single-scan FM-KFM technique on an active nanoelectronic device consisting of a 70 nm diameter InAs nanowire contacted by a pair of 120 nm thick electrodes.
Keywords: capacitive crosstalk; frequency modulation; Kalman filter; Kelvin probe force microscopy; sidebands